Simultaneous measurement of thickness and sound velocity of porous coatings based on the ultrasonic complex reflection coefficient. (October 2022) - Dou, Pan; Zou, Laisheng; Wu, Tonghai; Yu, Min; Reddyhoff, Tom; Peng, Zhongxiao
Abstract: The ultrasonic pulse-echo method is widely adopted in measuring coating thickness via parameter inversion of the reflection coefficient. However, the ultrasonic application to thermal barrier coatings (TBCs, as typically applied on aero-engine blades) remains a challenge, as the porous structure significantly attenuates sonic propagation, which is also difficult to characterize. In this article, a method that effectively addresses this issue without the need of the wave attenuation coefficient is presented. Specifically, the complex ultrasonic reflection coefficient can help calculate the coating-induced phase shift, which is found to linearly vary against the ultrasonic wave frequency. The slope of this linear function, depending on the structural porosity, enables simultaneous measurements of both the sound velocity and the thickness of the coating. Moreover, the effectiveness of the proposed method is verified by acoustic finite element simulations and experimental measurements of 8YSZ thermal barrier coatings.